2006
DOI: 10.1103/physrevb.73.224404
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen vacancies in the magnetic and dielectric properties of the high-dielectric-constant systemCaCu3Ti4O12: An electron-spin resonance study

Abstract: We report experiments of electron spin resonance ͑ESR͒ of Cu 2+ in polycrystalline samples of CaCu 3 Ti 4 O 12 post-annealed in different atmospheres. After being synthesized by solid state reaction, pellets of CaCu 3 Ti 4 O 12 were annealed for 24 h at 1000°C under air, Ar or O 2 . Our temperature dependent ESR data revealed for all samples nearly temperature independent g value ͑2.15͑1͒͒ and linewidth for T ӷ T N Ϸ 25 K. However, the values of ESR linewidth are strongly affected by the oxygen content in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 21 publications
6
32
0
Order By: Relevance
“…6. This conclusion is consistent with a previous dielectric measurement of pure CdCu 3 Ti 4 O 12 (ε ~9 × 10 3 at room temperature (100 kHz)) by Zuo et al [28], in contrast to the first report, ε=409, for pure CdCu 3 O-Cu-O. [29,30] In typical perovskite ferroelectrics, the dipole moment induced by the distortion of TiO 6 octahedron from its regular configuration plays an important role for the appearance of ferroelectricity.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…6. This conclusion is consistent with a previous dielectric measurement of pure CdCu 3 Ti 4 O 12 (ε ~9 × 10 3 at room temperature (100 kHz)) by Zuo et al [28], in contrast to the first report, ε=409, for pure CdCu 3 O-Cu-O. [29,30] In typical perovskite ferroelectrics, the dipole moment induced by the distortion of TiO 6 octahedron from its regular configuration plays an important role for the appearance of ferroelectricity.…”
Section: Introductionsupporting
confidence: 91%
“…[2] Furthermore an antiferromagnetic phase transition was observed at 25 K by magnetic susceptibility and specific heat measurements. [3] Compared with typical perovskite-type ferroelectrics such as BaTiO 3 and PbTiO 3 , the nature of this perovskite-related compound is very peculiar in exhibiting high dielectric constants over the wide range of temperature. The giant dielectric behavior seems to originate from an extrinsic origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9. Calibration of the intensity data using CaCu 3 Ti 4 O 12 as reference, 40 revealed that indeed all copper spins contribute to the ESR signal. The ESR intensity shows a pronounced broad maximum at around 6 K similar to the χ(T) data.…”
Section: E Electron Spin Resonancementioning
confidence: 99%
“…The broadening of the paramagnetic line may occur due to an additional internal magnetic field from the ferromagnetic LSMO component. In pure CCTO the ESR linewidth varies considerably with the change in the oxygen content while the absolute value of g-factor is independent of the annealing atmosphere: air, argon, or oxygen [39].…”
Section: Electron Spin Resonancementioning
confidence: 97%